Non-thermal, minimally invasive methods for the treatment of chronic venous insufficiency of the lower limbs – analysis of efficacy and safety - Szada-Borzyszkowski, Krzysztof; Kozyra, Klaudia; Kozieł-Kwit, Sylwia; Skowierzak, Filip; Lisik, Bartłomiej; Sado, Aleksandra; Wręczycki, Mariusz; Sawczuk, Kacper; Simlat, Aleksandra; Rogowska, Wiktoria (Journal of Education, Health and Sport, 2026)
Introduction Chronic venous insufficiency of the lower limbs (CVI) is a common disorder of the venous system, leading to significant clinical symptoms and reduced quality of life in patients. In recent years, there has been rapid development of minimally invasive endovascular methods, particularly non-thermal techniques, which provide an alternative to conventional surgical treatment and thermal ablation. Aim The aim of this study was to analyze the effectiveness and safety of non-thermal, minimally invasive methods for treating chronic venous insufficiency of the lower limbs, with particular emphasis on ultrasound-guided foam sclerotherapy (UGFS), cyanoacrylate adhesive embolization (CAC), and mechanochemical ablation (MOCA). Results Non-thermal methods for treating chronic venous insufficiency demonstrate high short-term effectiveness and a favorable safety profile. Foam sclerotherapy, cyanoacrylate adhesive embolization, and mechanochemical techniques enable effective closure of incompetent veins, significant symptom reduction, and improvement in quality of life, with minimal peri-procedural pain and a rapid return to daily activities. Conclusions Non-thermal, minimally invasive techniques constitute a safe and effective alternative to surgical treatment and thermal methods, particularly for patients who prefer less invasive approaches and shorter recovery times. Their limitation remains lower long-term durability compared to thermal ablation, which necessitates individualized method selection and further comparative studies.